Caregiver Burden Associated-Risk Factor of Chronic Kidney Disease Patients with Hemodialysis - Syahri, Rahmat Alfi; Usma, Said; Saputra, Irwan; Kamil, Hajjul; Nurjannah, Nurjannah (STRADA : Jurnal Ilmiah Kesehatan, 2020)
All respondents who were suitable for the inclusion criteria would automatically include into the study. Respondents must be a caregiver for one of his family members who underwent dialysis treatment in the center and signed informed consent for the study enrollment. Caregiver burden was assessed using standardized questionnaire based on Zarit Burden Scale and The Montgomery Borgotta Caregiver Burden Scale which consists of 39 questions. There were 40 respondents who included into the study with following results, the statistical analysis has been proved that significant relationship of gender and knowledge level was evident in the study with the high CB (p-value < 0.05) while age, education level, and treatment duration was not associated with CB in the study. The linkage between those risk factors must be considered in every circumstance for patient well-being since its relationship with higher CB was evident through the study